Stadt und Bildhauerei : 1. Bochumer Bildhauersymposium 1979/80. - Museum Bochum, Bochum (Bochum : Museum Bochum, 1981)
Christian, Abraham David ; Kolig, Cornelius ; Kozaric, Ivan ; Morellet, François ; Signer, Roman ; Szankowski, Maciej ; Spagnulo, Giuseppe ; Trantenroth, A.D. ; Veselý, Ales
Stadt und Bildhauerei : 1. Bochumer Bildhauersymposium 1979/80, Museum Bochum, Bochum, 1981
boek